Banking Stability and Financial Inclusion a Comparative Analysis of MENA Economies' Nonperforming Loans and Liquidity Risks - Mili, Hela (Journal of Posthumanism, 2025)
Financial inclusion has become an important global policy objective; however, it is still unknown how it will affect the stability of the banking industry overall, particularly given the precarious economic situation in the Middle East and North Africa (MENA) area. This study examines the possibility of impact of financial inclusion on two primary types of banking risk: liquidity risk and credit risk, as indicated by nonperforming loans (NPLs). A two-step Generalized Method of Moments (GMM) method is then applied to a panel dataset of MENA commercial banks covering the period from 2000–2024 in order to develop a composite index that captures several aspects of financial inclusion. According to the empirical evidence, financial inclusion has two impacts: on the one hand, it substantially decreases the quantity of non-performing loans (NPLs), that is indication of greater risque diversification and a rise in the deposit base; on the other hand, it seems to raise liquidity risk, probably as a consequence of the large number of small and short-term depositors. The outcomes indicate a moderate trade-off between credit and liquidity problems across several model parameters. The general conclusion of the study is that while financial inclusion increases asset quality, it also demands more developed systems for liquidity management. Therefore, regulators and policy makers are encouraged to pursue inclusive financial systems along with prudential liquidity measures to protect global financial stability